Novel SOLPS-ITER simulations of X-point target and snowflake divertors. (1st March 2023) - Cowley, C; Kuang, A Q; Moulton, D; Lore, J D; Canik, J; Umansky, M; Wigram, M; Ballinger, S; Lipschultz, B; Bonnin, X
Abstract: The design and understanding of alternative divertor configurations may be crucial for achieving acceptable steady-state heat and particle material loads for magnetic confinement fusion reactors. Multiple X-point alternative divertor geometries such as snowflakes and X-point targets have great potential in reducing power loads, but have not yet been simulated widely in codes with kinetic neutrals. This paper discusses recent changes made to the SOLPS-ITER code to allow for the simulation of X-point target and low-field side snowflake divertor geometries. Snowflake simulations using this method are presented, in addition to the first SOLPS-ITER simulation of the X-point target. Analysis of these results show reasonable consistency with the simple modelling and theoretical predictions, supporting the validity of the methodology implemented.